2013
DOI: 10.1038/ncb2871
|View full text |Cite
|
Sign up to set email alerts
|

SelR reverses Mical-mediated oxidation of actin to regulate F-actin dynamics

Abstract: Actin's polymerization properties are dramatically altered by oxidation of its conserved methionine (Met)-44 residue. Mediating this effect is a specific oxidation-reduction (Redox) enzyme, Mical, that works with Semaphorin repulsive guidance cues and selectively oxidizes Met-44. We now find that this actin regulatory process is reversible. Employing a genetic approach, we identified a specific methionine sulfoxide reductase enzyme SelR that opposes Mical Redox activity and Semaphorin/Plexin repulsion to direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
254
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(270 citation statements)
references
References 57 publications
(111 reference statements)
12
254
0
Order By: Relevance
“…They are widely expressed in nervous system and other tissues, including endothelial cells and cancer cells such as melanoma and HeLa cells 4, 5, 6, 7. Although MICAL family is identified as MICAL (1‐3) and MICAL‐like (‐L1, ‐L2) forms in mammals, its main functions were studied mostly in Drosophila 1, 3, 8. Normally, MICAL family members have four conserved domains: N‐terminal flavin adenine dinucleotide (FAD) binding domain, Lin11, Isl‐1 and Mec‐3 (LIM) domain, calponin homology (CH) domain and C‐terminal coiled‐coil (CC) domain.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely expressed in nervous system and other tissues, including endothelial cells and cancer cells such as melanoma and HeLa cells 4, 5, 6, 7. Although MICAL family is identified as MICAL (1‐3) and MICAL‐like (‐L1, ‐L2) forms in mammals, its main functions were studied mostly in Drosophila 1, 3, 8. Normally, MICAL family members have four conserved domains: N‐terminal flavin adenine dinucleotide (FAD) binding domain, Lin11, Isl‐1 and Mec‐3 (LIM) domain, calponin homology (CH) domain and C‐terminal coiled‐coil (CC) domain.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MICAL-mediated actin oxidation is selectively reversed by methionine sulfoxide reductases (SelR in Drosophila, MsrB proteins in mammals), which prevent F-actin disassembly induced by MICALs in vitro (Hung et al, 2013;Lee et al, 2013). Consistent with this, SelR counteracts Mical in multiple actin-dependent cellular processes in Drosophila, including axon guidance, synaptogenesis, muscle organization and mechanosensory development (Hung et al, 2013). In mammals, MsrB1 has a regulatory role as a MICAL1 antagonist in orchestrating actin dynamics and macrophage function (Lee et al, 2013).…”
Section: Mechanisms Of Mical-induced Actin Depolymerizationmentioning
confidence: 95%
“…In addition, a direct contact between MICALs and F-actin appears to be compulsory for depolymerization, whereas incubation with high concentrations of H 2 O 2 (40 mM) alone are insufficient to depolymerize actin filaments (Frémont et al, 2017;Hung et al, 2011). Interestingly, MICAL-mediated actin oxidation is selectively reversed by methionine sulfoxide reductases (SelR in Drosophila, MsrB proteins in mammals), which prevent F-actin disassembly induced by MICALs in vitro (Hung et al, 2013;Lee et al, 2013). Consistent with this, SelR counteracts Mical in multiple actin-dependent cellular processes in Drosophila, including axon guidance, synaptogenesis, muscle organization and mechanosensory development (Hung et al, 2013).…”
Section: Mechanisms Of Mical-induced Actin Depolymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that members of the MICAL family of redox enzymes (Zhou et al, 2011) can bind to the cytosolic part of plexins and induce F-actin disassembly by mediating the post-translational oxidation of actin filament subunits (Hung et al, 2010. Intriguingly, this process is antagonised by the methionine sulfoxide reductase SelR, which reduces oxidised actin and thereby promotes F-actin assembly (Hung et al, 2013). MICALs and SelR thus provide plexin receptors with the ability to directly redox modify F-actin upon semaphorin binding.…”
Section: Mechanisms Of Intracellular Signallingmentioning
confidence: 99%